Peningkatan Kemandirian Lansia dalam Manajemen Penyakit Kronis Melalui Edukasi Partisipatif di Kelurahan Kuin Cerucuk - Alessandra Dielfiony Sipayung; Era Indrian; Fransiska Natasha Fardi; Norwita Dwi Priyono; Stefani Stefani; Yosafat Eliahkim Selan; Yunia Angela M; Sumiati Hartati; Maria Frani Ayu Andari Dias (Institut Kesehatan Suaka Insan, 2026)
Elderly individuals in Kuin Cerucuk are susceptible to chronic diseases, particularly hypertension and diabetes mellitus, which are exacerbated by suboptimal health management and cultural dietary habits. This community service aimed to improve elderly independence in chronic disease management through a participatory education program. The implementation method involved a community-based approach consisting of three stages: assessment, educational intervention, and evaluation. The program utilized